Mission & science missiology reviseed, 1850-1940 - Dujardin, Carine; Prudhomme, Claude 1947- (Leuven University Press, 2015)
Science as an instrument to justify religious missions in secular society. The relationship between religion and science is complex and continues to be a topical issue. However, it is seldom zoomed in on from both Protestant and Catholic perspectives. By doing so the contributing authors in this collection gain new insights into the origin and development of missiology. 0Missiology is described in this book as a "project of modernity," a contemporary form of apologetics. "Scientific apologetics" was the way to justify missions in a society that was rapidly becoming secularized. Mission & Science deals with the interaction between new scientific disciplines (historiography, geography, ethnology, anthropology, linguistics) and new scientific insights (Darwin's evolutionary theory, heliocentrism), as well as the role of the papacy and what inspired missionary practice (first in China and the Far East and later in Africa). The renewed missiology has in turn influenced the missionary practice of the twentieth century, guided by apostolic policy. Some "missionary scholars" have even had a significant influence on the scientific discourse of their time
Beiträge teilweise englisch, teilweise französisch
Keywords: Geschichte 1850-1940; Missionswissenschaft; Naturwissenschaften; Missionstheologie; Aufsatzsammlung